Treatment of central giant cell granuloma in children with denosumab. Issue 3 (21st October 2020) - Choe, Michelle; Smith, Valeria; Okcu, M. Fatih; Wulff, Jade; Gruner, Stephanie; Huisman, Thierry A.G.M.; Venkatramani, Rajkumar
Abstract: Central giant cell granuloma (CGCG) is a benign but locally aggressive intraosseous lesion of the mandible. Historically, it is treated by curettage or resection. Medical therapy is indicated when surgery is associated with increased morbidity or in adjuvant setting to decrease recurrence. Treatment of CGCG with denosumab, a receptor activator of nuclear factor kappa‐beta (RANK) ligand inhibitor, is not well studied, especially in children. Here, we describe our experience with the use of denosumab in the treatment of six children with CGCG. All patients had a favorable response with manageable side effects, which suggests that denosumab is an effective treatment option without increased morbidity.